Preclinical evaluation of a diabody-based 177Lu-radioimmunoconjugate for CD22-directed radioimmunotherapy in a non-Hodgkin lymphoma mouse model - Weber, Tobias; Bötticher, Benedikt; Arndt, Michaela; Mier, Walter; Sauter, Max; Exner, Evelyn; Keller, Armin; Krämer, Susanne; Leotta, Karin; Wischnjow, Artjom; Jäger, Dirk; Haberkorn, Uwe; et al. (Cancer letters, 2016)
Radioimmunotherapy is considered as treatment option in recurrent and/or refractory B-cell non-Hodgkin lymphoma (B-NHL). To overcome the dose limiting bone marrow toxicity of IgG-based radioimmunoconjugates (RICs), we modified a humanized diabody with 5-, 10-, or 20-kDa polyethylene glycol (PEG) for CD22-targeted radioimmunotherapy using the low-energy β-emitter lutetium-177 (177Lu). A favorable pharmacokinetic profile was observed for the 10-kDa-PEG-diabody in nude mice being xenografted with subcutaneous human Burkitt lymphoma. Even at high doses of 16 MBq this diabody RIC was well tolerated by NOD Rag1null IL2rγnull (NRG) mice and did not reveal signs of organ long-term toxicity 80 days post injection. Combination therapy of the diabody RIC with unconjugated anti-CD20 Rituximab demonstrated therapeutic efficacy in established disseminated mantle cell lymphoma xenograft models. When compared with the combination of the IgG formatted 177Lu anti-CD22 antibody and Rituximab, dual targeted therapy with the diabody RIC achieved an improved reduction of disease burden in the first nine days following treatment. The data indicate that the PEGylated anti-CD22 diabody may have potential for extending the repertoire of radiopharmaceuticals for the treatment of patients with B-NHL.